Analisis Model Pembelajaran Picture and Picture dalam Meningkatkan Pemahaman Siswa terhadap Materi Al-Qur’an dan Hadis - Kariadinata, Rahayu; Azizah, Habibah Nur; Rahman, Dede Arif; Nurlela, Risma; Nugraha, Taufik Agung (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to analyze the effectiveness of the Picture and Picture learning model in improving students’ understanding of Qur’an and Hadith subjects. The study is motivated by the dominance of conventional teaching methods, which often result in suboptimal conceptual comprehension among students. Employing a quantitative approach with a One Group Pretest-Posttest design, the research utilized an objective test administered before and after the implementation of the learning model. The data were analyzed using the Wilcoxon test due to non-normal distribution. The findings revealed a significant difference between pretest and posttest scores (p = 0.000), indicating that the Picture and Picture model is effective in enhancing students’ understanding. This model successfully translates abstract concepts in Qur’an and Hadith into more concrete representations, fosters student engagement, and positively influences cognitive, affective, and psychomotor domains.